E2F1 proteolysis via SCF‐cyclin F underlies synthetic lethality between cyclin F loss and Chk1 inhibition. (19th August 2019) - Burdova, Kamila; Yang, Hongbin; Faedda, Roberta; Hume, Samuel; Chauhan, Jagat; Ebner, Daniel; Kessler, Benedikt M; Vendrell, Iolanda; Drewry, David H; Wells, Carrow I; Hatch, Stephanie B; Dianov, Grigory L; et al.
Abstract: Cyclins are central engines of cell cycle progression in conjunction with cyclin‐dependent kinases (CDKs). Among the different cyclins controlling cell cycle progression, cyclin F does not partner with a CDK, but instead forms via its F‐box domain an SCF (Skp1‐Cul1‐F‐box)‐type E3 ubiquitin ligase module. Although various substrates of cyclin F have been identified, the vulnerabilities of cells lacking cyclin F are not known. Thus, we assessed viability of cells lacking cyclin F upon challenging them with more than 180 different kinase inhibitors. The screen revealed a striking synthetic lethality between Chk1 inhibition and cyclin F loss. Chk1 inhibition in cells lacking cyclin F leads to DNA replication catastrophe. Replication catastrophe depends on accumulation of the transcription factor E2F1 in cyclin F‐depleted cells. We find that SCF‐cyclin F controls E2F1 ubiquitylation and degradation during the G2/M phase of the cell cycle and upon challenging cells with Chk1 inhibitors. Thus, Cyclin F restricts E2F1 activity during the cell cycle and upon checkpoint inhibition to prevent DNA replication stress. Our findings pave the way for patient selection in the clinical use of checkpoint inhibitors. Synopsis: A kinase inhibitor screen for synthetic lethality in cells lacking the ubiquitin ligase adaptor Cyclin F leads to the identification of E2F1 as new SCF‐Cyclin F substrate, whose unrestricted activity promotes catastrophic replication stress upon checkpoint suppression with Chk1 inhibitors. A screen to identify vulnerabilities of cells lacking cyclin F identifies Chk1 inhibitors as primary hits. Cyclin F loss predisposes cells to the toxic effect of Chk1i by inducing DNA replication catastrophe. Aberrant accumulation of E2F1 upon cyclin F loss promotes DNA damage upon Chk1 inhibition. Lack of cyclin F prevents degradation of E2F1 in G2/M and upon Chk1 inhibitors. A non‐degradable E2F1 lacking a CY motif induces cell death and DNA replication stress upon Chk1 inhibition. Abstract : A kinase inhibitor screen reveals that Chk1‐dependent checkpoint responses are required to prevent catastrophic replication stress caused by unrestricted E2F1 activity in cells lacking Cyclin F.